Incidence of Co-Trimoxazole-Induced Hyperkalemia in a Tertiary Care Hospital - Rana M Al AdAwi (16515256) (2021)
Background Co-trimoxazole is a broad-spectrum antibiotic associated with hyperkalemia. Objective: To determine the incidence of hyperkalemia and its risk factors in patients receiving co-trimoxazole. Materials and Methods A retrospective observational study involving all patients who received co-trimoxazole between 1 January 2012 and 1 January 2013 was conducted. Subjects were identified through a list generated from a computerized pharmacy system. The patients’ demographic and clinical characteristics were retrieved from electronic medical records. Data were analyzed using univariate and multivariate logistic regression. Results One hundred sixty-one patients fulfilled the eligibility criteria. Of these, 46 (28.6%) experienced hyperkalemia. Around 35 (76%) of the patients who experienced hyperkalemia received co-administered medications that might induce hyperkalemia. The co-administration of co-trimoxazole with other medications that may induce hyperkalemia was found to be associated with higher incidence of hyperkalemia when compared to co-trimoxazole administration alone [adjusted OR 3.2, 95% CI (1.4– 7.3), p=0.005]. Additionally, age > 60 years was associated with an increased risk of hyperkalemia when compared to younger age group 18– 39 years [adjusted OR 6.5, 95% CI (2.1– 19.7); p=0.001]. Conclusion Co-trimoxazole use is associated with high incidence of hyperkalemia, especially among older patients and those receiving it in combination with other medications that might contribute to hyperkalemia development such as calcineurin inhibitors and β-blockers. Other Information Published in: Risk Management and Healthcare Policy License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.2147/rmhp.s283471